2019
DOI: 10.1016/j.autneu.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical morphometric predictors of autonomic dysfunction in generalized anxiety disorder

Abstract: Generalized anxiety disorder (GAD) is associated with both autonomic dysfunction, notably decreased vagally-mediated heart rate variability (vmHRV), and neurostructural abnormalities. Regional differences in brain morphometry correlate with vmHRV in healthy individuals. Here, we tested the hypothesis that specific focal abnormalities in cortical structure in GAD underpin decreased vmHRV. Adult female patients with GAD (n = 17) and matched controls (n = 18) underwent structural magnetic resonance imaging after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 91 publications
1
60
0
2
Order By: Relevance
“…An extensive literature has shown that a wide range of psychiatric disorders, especially anxiety and depression, can accompany migraine [4,[47][48][49]. Previous studies revealed cortical abnormalities in depression [35,50,51] and anxiety disorders [52][53][54][55]. However, these psychiatric problems are often under-diagnosed and have not been thoroughly assessed in CTh studies in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature has shown that a wide range of psychiatric disorders, especially anxiety and depression, can accompany migraine [4,[47][48][49]. Previous studies revealed cortical abnormalities in depression [35,50,51] and anxiety disorders [52][53][54][55]. However, these psychiatric problems are often under-diagnosed and have not been thoroughly assessed in CTh studies in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies also reveal heterogeneity in both structural and functional measures of brain regions involved in cognitive control among pathological worriers. For example, Makovac et al (2016a) and Carnevali et al (2019) found individuals with GAD to have lower average gray matter volume than healthy controls in regions of the PFC involved in top-down control. However, in contrast, Mohlman et al (2009) found medial orbital PFC volume to be positively associated with scores on the Penn State Worry Questionnaire (PSWQ).…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly given such findings, studies have linked low resting vmHRV to pathological worry (e.g., Thayer et al, 1996 ; Carnevali et al, 2019 ). A meta-analysis by Chalmers et al (2014) shows that individuals with GAD do indeed have lower resting vmHRV on average than controls (Hedge’s g = −0.55).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently shown that resting-state HRV is associated with the morphology of the brain across regions of interest [ROI], indexed by cerebral cortical thickness [CT] (Carnevali et al, 2019;Koenig et al, 2018;Lin et al, Woodward, Kaloupek, Schaer, Martinez, & Eliez, 2008;Yoo et al, 2017). CT is considered to reflect cellular aspects of the cortical organization (Lerch, 2001).…”
Section: Introductionmentioning
confidence: 99%